Presenting a Validated Mid-Semester Evaluation of College Teaching to Improve Online Teaching - Byrne, Virginia L; Donlan, Alice E (Online Learning, 2020)
Formative feedback from students can help college instructors improve their online teaching practices - especially instructors who are new to online teaching. Prior research indicates that mid-semester formative evaluations of college teaching are a promising, low-cost solution to providing online instructors with in-the-moment feedback. However, existing instruments suffer from issues of validity and bias, and fail to align with evidence-based strategies. In this paper, we present psychometric results from a pilot study of our research-based Mid-Semester Evaluation of College Teaching (MSECT) to assist online educators in gathering student input to improve their online teaching and classroom climate.